Universal protection of the right to equality - Lousada Arochena, José Fernando (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2020)
Abstract. The right to equality of human beings and the prohibition of discrimination recognized in international human rights treatys require effective guardianship mechanisms. The study analyzes the organizations and procedures established at the universal level under the generic mandate of the United Nations and in the Core international human rights instruments. In particular, the study focus in the procedure complaints from individuals in the Convention on the Elimination of All Forms of Discrimination against Women (1979), the Convention on the Elimination of All Forms of Racial Discrimination (1965), and the Convention on the Rights of Persons with Disabilities (2006). Finally, the effectiveness in Spain of the Committee’s views on the elimination of all forms of discrimination against women is analyzed too.